Synchronization of Inclusive Education Policies: A Comparative Study of the Independent Curriculum Mandate and the Absence of Local Regulations in Sukoharjo Regency - Deden Mutakin (Fakultas Ilmu Pendidikan, 2026)
Inclusive education is a human rights mandate that is reinforced through the Merdeka Curriculum with the instrument of Differentiated Learning. However, there is a significant gap between national policy and local implementation in Sukoharjo Regency. This study aims to evaluate the synchronization of central and regional policies and identify the root causes of the ineffectiveness of teacher training in handling Students with Special Needs (PDBK). This study uses a qualitative approach with library research and unstructured interviews. Data were analyzed using content analysis and comparative techniques to examine regulations and inclusive education practices in several regions. The results of the study show that there is a legal gap due to the absence of a specific Regent Regulation governing the implementation of inclusive education, thus creating a phenomenon of “inclusion in the shadows” in public elementary schools. The teacher training program is considered to have no impact because it is theoretical and normative in nature, without continuous post-training assistance. In addition, the “Inclusion Studio” innovation in Sukoharjo is still fragmented and has not been pedagogically integrated into the formal school system. This study recommends accelerating the formation of regional regulations and the institutionalization of Disability Service Units to ensure budget support, the provision of Special Guidance Teachers, and legal protection for inclusive learning innovations in schools.